Magic Boom Chemical: A Tracking Marker-Based Approach in Developing Chemical Molecule Textbook - Tina Tri Wulansari; Pebiansyah Hafsari; Ratih Fenty Anggriani Bintoro; Yuli Fitrianto; Gunawan Gunawan; Nyoman Santiyadnya; Reza Andrea; Syafei Karim; Dewi Rostia; Guntur Arie Wibowo; Tri Hannanto Saputra; Maria Floriana Ping (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
In Traditional teaching methods for chemical molecules, which rely on textbooks and physical modeling tools, face challenges in providing an engaging and comprehensive learning experience. This study introduces